A critical analysis of the impact of the constitution [Amendment no. 20] on the regulation of abortion in Zimbabwe - Bare, Claude E. T. (Midlands State University, 2017)
This dissertation sought to critically analyse the impact of the Constitution [Amendment no. 20] on the law regulating abortions in Zimbabwe, taking into account that the Constitution provides for the protection of reproductive rights and adopts the concept of Constitutionalism. The study brought to attention crisis that the prolife Abortion law conflicts with abortion practices in reality as there are high numbers of abortions being performed in society and this is an indication of the existence of a legal problem. Further, the study established that the turn to constitutionalism and the protection of reproductive rights make the prolife abortion law untenable. Therefore, it has being recommended that the Abortion law be changed to provide for choice.